2021
DOI: 10.22271/allresearch.2021.v7.i7d.8772
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual intelligence and mindfulness as predictors of life satisfaction among youth of Jammu and Kashmir

Abstract: This study investigated the relationship among spiritual intelligence mindfulness and life satisfaction among young adults. The sample consisted of 168 young adults. Spiritual Intelligence Questionnaire (SIQ) by Abdollahzadeh et al. ( 2009) [1] Mindful Attention Awareness Scale (MASS) by Brown and Ryan (2003) [7] Satisfaction with Life Scale (SWLS) by Diener et al., (1985) [12] were used to study the variables. Pearson product moment correlation and stepwise regression were applied to analyze the data. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…This view, in addition to the teachers' strong influence on the pupils makes SI a critical success factor (Pishghadam et al, 2022). Other finding (Singh and Sinha, 2013) in the educational literature also supports that SI can potentially be inculcated via training and deliberate practice, making is an important domain in education literature. Consistent with the growing research interest on SI, Singla et al (2021) found a strong correlation with teachers' quality of work life, through utilization of spiritual resources for spiritual coping.…”
Section: Introductionmentioning
confidence: 73%
“…This view, in addition to the teachers' strong influence on the pupils makes SI a critical success factor (Pishghadam et al, 2022). Other finding (Singh and Sinha, 2013) in the educational literature also supports that SI can potentially be inculcated via training and deliberate practice, making is an important domain in education literature. Consistent with the growing research interest on SI, Singla et al (2021) found a strong correlation with teachers' quality of work life, through utilization of spiritual resources for spiritual coping.…”
Section: Introductionmentioning
confidence: 73%
“…Mindfulness, characterized by a present-focused awareness and acceptance, has been demonstrated to mediate important psychological factors such as internal control and the presence of meaning in life, thereby fostering life satisfaction (Yuan et al, 2021). This effect has been observed across diverse groups, including nursing students (Asik & Albayrak, 2021) and youth (Singh & Gupta, 2021), highlighting the universal benefits of mindfulness practices.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have indicated that mindfulness can positively impact life satisfaction by mediating factors such as internal control and the presence of meaning in life (Yuan et al, 2021). Furthermore, mindfulness has been linked to higher life satisfaction levels among various groups, such as nursing students (Asik & Albayrak, 2021) and youth (Singh & Gupta, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Menurut Howard Gardner, kecerdasan ialah kemampuan untuk menciptakan sebuah karya/produk atau memberikan pelayanan yang bermutu. Ia merupakan seperangkat skill untuk dapat menyelesaikan problematika pekerjaan, tugas maupun lainnya dalam hidup sehari-hari (Singh, 2013). Kemampuan dasar inilah yang menuntun manusia dalam tindaktanduknya sehari-hari (Ronel, 2008).…”
Section: Kecerdasan Spiritualunclassified
“…Ini berbeda dengan Emotional Quotient (EQ) dan Intellectual Quotient (IQ) yang berbasis pada bagian otak tertentu. SQ menyinkronkan bagian-bagian kecerdasan lainnya di otak (Singh, 2013).…”
Section: Kecerdasan Spiritualunclassified